Incidence of Culicoides species in Maiduguri Nigeria - Abdullahi A. Biu; Hyellamada J. Chama; Jummai Musa; ThankGod E. Onyiche (Ntec Specialist, 2024)
Background: Culicoides are Diptera of the Family Ceratopogonidae commonly called biting midges or nosee-ums with the capacity as biological vectors of pathogens causing notifiable diseases. Objectives: We surveyed to ascertain the presence and species composition of Culicoides species from various locations and catch points in Maiduguri, Nigeria. Methodology: Culicoides insects were trapped from the selected locations and study points using laboratory-designed sticky traps made of wooden cardboard, painted bright yellow, and coated thinly with petroleum jelly (Vaseline®) which serves as an adhesive. Results: The incidence of Culicoides species between August and November in this study revealed a total catch of 34 using the sticky board trapping with Culicoides bolitinos having 32 (94.1%) and C. engubandei 2 (5.9%). Distribution of catches based on study location/foci and/or catch points/loci showed the highest incidence on the University of Maiduguri livestock farm with 11 (32.4%) and drinking troughs with 15 (44.1%). In conclusion, this study has revealed a location cum catch point dependent incidence of Culicoides in Maiduguri, Nigeria. Conclusion: Despite the low incidence of Culicoides species, we established their presence across the different study locations. We recommend that further studies be conducted to ascertain the seasonal presence as well as their preferred feeding host in the study locations.